An In-Depth Analysis of Smart Service Systems: Exploring Concepts and Overcoming Challenges - Angga Prasetya; Rusman Wibawa; Paranita Riche (ITEJ (Information Technology Engineering Journals), 2023)
This comprehensive survey delves into the realm of Smart Service Systems, aiming to provide an in-depth analysis of its fundamental concepts and address the challenges faced in its implementation. Smart Service Systems represent a transformative paradigm that leverages cutting-edge technologies, such as artificial intelligence, Internet of Things, and cloud computing, to enhance the efficiency, effectiveness, and personalization of service delivery. The paper explores the key components and underlying principles that form the backbone of these systems, shedding light on their potential applications and benefits across various domains. However, the realization of Smart Service Systems comes with a set of formidable challenges that need to be tackled. These challenges encompass technical, ethical, legal, and societal aspects, among others. By examining and understanding these obstacles, the paper aims to propose potential strategies and solutions to overcome them. The analysis is further enriched with case studies and real-world examples to provide valuable insights for researchers, practitioners, and policymakers. In conclusion, this survey serves as a comprehensive resource for the exploration of Smart Service Systems, illuminating the path towards harnessing their full potential while addressing the complexities they present. It is hoped that this work will inspire further research and foster advancements in this burgeoning field, ultimately leading to the widespread adoption and integration of intelligent service systems for a more efficient and sustainable future.